PENGARUH PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) JENIS CHATGPT DAN MINAT BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS X MANAJEMEN PERKANTORAN DAN LAYANAN BISNIS DI SMK NEGERI 7 MEDAN T.A 2024/2025 - Ananda Sry Aulia Rizky; Tauada Silalahi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This study aims to determine the effect of the use of Artificial Intelligence (AI) of the ChatGPT type and learning interest on the learning outcomes of class X students in Office Management and Business Services (MPLB) at SMK Negeri 7 Medan in the 2024/2025 academic year. This study used a quantitative approach with an ex-post facto type. The sample in this study consisted of 69 respondents selected using a purposive sampling technique. Data collection techniques used questionnaires and documentation of daily test scores. Data analysis was performed using multiple linear regression tests, partial tests (t-tests), simultaneous tests (F-tests), and coefficients of determination (R²) using SPSS 26. The analysis results show that the variable Use of Artificial Intelligence of the ChatGPT type (X1) has a positive and significant effect on student learning outcomes with a t-value (calculated) of 19.630 and a Sig. 0.000 <0.05. Similarly, the learning interest variable (X2) also had a positive and significant effect on learning outcomes, with a t-test value of 41.867 and a Sig. 0.000 <0.05. Simultaneously, the F-test value was 1005.627 with a Sig. 0.000 <0.05, indicating that the use of ChatGPT and learning interest together had a significant effect on learning outcomes. The coefficient of determination (R²) of 0.968 indicates that 96.8% of the variation in learning outcomes can be explained by the two independent variables, while the remaining 3.2% is explained by other factors outside this study. Thus, it can be concluded that the use of ChatGPT Artificial Intelligence and learning interest have a positive and significant effect, both partially and simultaneously, on improving student learning outcomes. This study emphasizes the importance of integrating AI-based digital technology and fostering student learning interest to support the achievement of optimal learning outcomes.